Conservação e valores sob a perspectiva do patrimônio na Alemanha: a prática da reconstrução - Roberto Flavio Sant'ana de Almeida (2013)
This work has as theme the debate about the reconstruction of monuments in Germany. The objective is to identify the relationships between the values of the local community and the repercussions of this intervention in monuments. Initially, it presents a brief history of preservation of monuments in Germany. It then analyzes the discussion held in the city of Heidelberg in the late nineteenth century about the possible reconstruction of the city castle. Noteworthy are the work of the art historians, Alois Riegl and Georg Dehio, which contributed to the foundation of the theory of preservation in Germany. It also analyzes the recent debate held in Berlin about the demolition of the Palace of the Republic, which was the seat of the socialist government of German Democratic Republic; for the reconstruction of the Royal Palace (Stadtschloss), which was the residence of the governors before the unification of that country. For this, it does a bibliographic and documentary research, analyzing facts and opinions from different experts on the theme. The case studies show the controversies and dilemmas that emerged in the debates about reconstruction. Finally, it suggests that certain values of the society are decisive in choosing the reconstruction and they can relate to the cultural identity of the nation. The prevailing values may also relate to the political aspects of the historical context of the monument.